Physiological plasticity in zebra finch color varieties mitigates DNA damage under oxidative stress - Cristiana I. Marques; Sol Rodríguez-Martínez; Pedro Miguel Araújo; Sandra Afonso; Mohammed Zougagh; Ángel Ríos; Miguel Carneiro; Ismael Galván (iScience)
Summary: Melanins are fundamental vertebrate pigments. Pheomelanin synthesis utilizes cysteine, a precursor for the antioxidant glutathione. Sustained pheomelanin synthesis may thus reduce cysteine availability for antioxidant defenses, resulting in a trade-off most relevant in stressful environments. Here, we investigated how pheomelanin may influence birds’ response to oxidative stress. We began by determining the genetic bases of three independent melanin-based zebra finch varieties. Two previously established melanin genes can explain blackcheek (NDP) and white (EDNRB2) mutations, while a novel pigmentation gene (ZNRF3) was associated with the eumelanin-to-pheomelanin shift in the orange-breasted phenotype. Orange-breasted individuals exhibited higher DNA damage and a gene expression profile compatible with cellular redox imbalance. During oxidative stress, these birds minimized DNA damage and changed pheomelanin concentration, consistent with cysteine/glutathione economization. Further analyses revealed downregulation of glutathione S-transferases in pheomelanic morphs across species. We propose that pheomelanic birds might have an adaptive built-in physiological plasticity under environmental oxidative stress.